2016
DOI: 10.5578/keg.9475
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Efficacy Belief Scale for Planning and Organizing Educational Trips to Out of School Settings

Abstract: ABSTRACT:The aim of this research study was to develop a scale for self-efficacy beliefs in planning and organizing educational trips to out of school environments. First of all, relevant literature on developing a scale was reviewed in this stage. Within this context, the researcher identified total 45 initial items. The draft scale consisting of total 39 items for pre-implementation stage was administered to 358 pre-service teachers in their fourth year in Giresun Education Faculty in 2013-2014 academic year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 26 publications
1
14
0
5
Order By: Relevance
“…The scale's item-total correlation coefficients changed between 0.585 and 0.759. As a result of the reliability analysis, the scale's Cronbach Alfa reliability coefficient was calculated as 0.931, the Guttmann Split-Half value was 0.889 and the Spearman Brown reliability coefficient was 0.889 (Bozdoğan, 2016). These results revealed that the scale's reliability was quite high, as each item in the scale met the scale's need to measure the features at a significant level (see Appendix 3).…”
Section: Data Collection Toolsmentioning
confidence: 91%
“…The scale's item-total correlation coefficients changed between 0.585 and 0.759. As a result of the reliability analysis, the scale's Cronbach Alfa reliability coefficient was calculated as 0.931, the Guttmann Split-Half value was 0.889 and the Spearman Brown reliability coefficient was 0.889 (Bozdoğan, 2016). These results revealed that the scale's reliability was quite high, as each item in the scale met the scale's need to measure the features at a significant level (see Appendix 3).…”
Section: Data Collection Toolsmentioning
confidence: 91%
“…SSOET which is composed of total 30 items, 17 positive and 13 negative items, is a 5 point Likert type scale. The scale's Cronbach's Alfa reliability coefficient was calculated to be 0,931 (Bozdoğan, 2015).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Öğretmenlerin öz yeterlilik inançları Bozdoğan (2016)'nın öğretmenler için geliştirmiş olduğu "Öz-yeterlilik İnancı Ölçeği" kullanılarak ortaya çıkarılmaya çalışılmıştır. Bu bağlamda oluşturduğumuz veri toplama aracının ilk bölümünü kişisel bilgiler, ikinci bölümünü ise Bozdoğanın ölçeği oluşturmaktadır.…”
Section: Veri Toplama Aracıunclassified
“…Tespit edilen bu değerler ile faktör analizinin uygunluğu görülmüştür. Açımlayıcı faktör analizi neticesinde, tüm bileşenlerin açıkladığı %66.66'lık varyansın büyük bir kısmı (yarıdan fazlası) olan %36.16'lık bölümünün birinci boyut ile açıklanması ile Bozdoğan (2016)'nın da çalışmasında belirttiği gibi bu araştırma için uygulanan ölçeğin tek faktörlü sayılabileceği kabul edilmiştir. Ölçeğin güvenirlik analizi neticesinde Cronbach Alpha değeri 0,91 olarak belirlenmiştir.…”
Section: Veri Toplama Aracıunclassified
See 1 more Smart Citation